Agronomical and quality differences of four fig cultivars grown in Brazil - Ferraz, Rafael Augusto; Leonel, Sarita [UNESP]; Souza, Jackson Mirellys Azevêdo [UNESP]; Modesto, Joyce Helena [UNESP]; Ferreira, Rafael Bibiano [UNESP]; de Souza Silva, Marcelo [UNESP] (Universidade Estadual de Londrina, 2021)
Figs consumption date back to the beginnings of civilization. Currently, consumers have become more demanding about quality of fruits, and figs are then highly indicated, since it is rich in nutrients, making them a great addition to a healthy diet. Although there is only one commercial fig cultivar that is commonly grown in Brazil, different cultivars should be considered for the diversification of fig production with regards to their yield and fruit quality. This research aimed at evaluating growth, yield, physicochemical characteristics and bioactive compounds of figs grown in Brazil. Then, four cultivars (Roxo de Valinhos, White Genova, PI-189 and Troyano) were studied to determine canopy volume, productive efficiency, soluble solids - SS, pH, titratable acidity - TA, SS/TA ratio, sugars, ascorbic acid, phenolic compounds, pigments and antioxidant activity. The cv. White Genova presented the highest canopy volume, while 'Roxo de Valinhos', 'PI-189' and 'Troyano' performed the greatest productive efficiency. The cvs. Roxo de Valinhos, White Genova and Troyano produced fruits with higher content of SS, reducing sugars and SS/TA ratio, while the fruits of 'PI-189' and 'Roxo de Valinhos' contained the highest levels of antioxidant activity. PCA enabled to differentiate the studied cultivars, which evidenced that PI-189 was the most different of all.
Diferenças agronômicas e qualidade de quatro cultivares de figo cultivados no Brasil
Keywords: Antioxidants; Ficus carica L; Phenolic compounds; Tree performance; Yield